“Gerakan Tebar Lele”: Pemberdayaan Masyarakat dalam Pengendalian DBD Melalui Pemanfaatan Ikan Lele sebagai Predator Larva Nyamuk - Rulita Maulidya; Handayani, Lia; Syahputra, Faisal; Sari, Mayang (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
The "Gerakan Tebar Lele" (Catfish Release Movement) is a community empowerment program aimed at controlling Dengue Hemorrhagic Fever (DHF) by utilizing catfish (Clarias sp.) as a natural predator of mosquito larvae. This initiative was carried out in Gampong Ujong XII, Ingin Jaya District, Aceh Besar, to increase public awareness and participation in environmentally friendly vector control. The implementation methods included public education, distribution of catfish seedlings, and monitoring the predation effectiveness of catfish on mosquito larvae in water storage areas. The results indicate increased community knowledge of ecological-based DHF control methods and a reduction in mosquito larvae populations in areas where catfish were introduced. This program is expected to serve as a sustainable alternative solution to reduce DHF cases in the region.